Abortion, opposing viewpoints - Szumski, Bonnie, 1958- (St. Paul, Minn. : Greenhaven Press, 1986)
Presents opposing viewpoints about various aspects of abortion, including its morality and legality. Includes critical thinking skill activities and a list of organizations to contact.
Includes bibliographies and index.
Keywords: Abortion -- United States; Abortion -- Moral and ethical aspects; Abortion